REVIEW OF FUNDING PROCEDURES ON PT FIFGROUP CILEGON BRANCH - Fitroh, Laila; Arisa, Lisa; Febrianti, Dian; Ekkiwinatha, Novan (Review of Accounting and Taxation, 2024)
Purpose - This research aims to describe the procedures for granting credit to Fifgroup companies in Cilegon Design/methodology/approach - Financing credit sales of Honda motorcycles to PT. FIFGROUP uses a system and credit financing procedures. The purpose of this study is (1) to analyze the effectiveness of procedures for providing credit funds to customers at PT. FIFGROUP Cilegon Branch (2) To analyze the customer's bad credit control system PT. FIFGROUP Celeron Branch Finding - Observations were made on the results of this study shows In analyzing the feasibility of granting credit to consumers, besides using 5C analysis the company also uses five parameters feasibility in analyzing whether or not the prospective debtor is financed credit, this proves that the company has carried out the process credit approval in accordance with procedures established by the company. Appropriate division of tasks and segregation of functions is control internal company which is one way to minimize risk uncollectible accounts receivable.